2018
DOI: 10.1111/liv.13929
|View full text |Cite
|
Sign up to set email alerts
|

Bacterascites: A study of clinical features, microbiological findings, and clinical significance

Abstract: BackgroundKnowledge about bacterascites is limited and management guidelines are based on small patient series. The purpose of this study was to add further insight into the clinical characteristics, microbiological findings, and prognosis of patients diagnosed with bacterascites.MethodsRetrospective analysis of patients with advanced chronic liver disease diagnosed with bacterascites and SBP between January 2003 and August 2016.ResultsIn this study, 123 patients were included with 142 episodes of bacterascite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 40 publications
3
32
2
Order By: Relevance
“…In our cohort, Gram‐negative bacteria were frequently isolated in culture‐positive SBP patients, which is consistent with the result of a previous report . However, Gram‐positive bacteria were the most frequent type of strain in bacterascites patients, and this result is in line with the findings of recent studies of bacterascites . Patients with cirrhosis are susceptible to various infections that may be caused by bacteria with low virulence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our cohort, Gram‐negative bacteria were frequently isolated in culture‐positive SBP patients, which is consistent with the result of a previous report . However, Gram‐positive bacteria were the most frequent type of strain in bacterascites patients, and this result is in line with the findings of recent studies of bacterascites . Patients with cirrhosis are susceptible to various infections that may be caused by bacteria with low virulence.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, few studies of bacterascites have been reported; therefore, knowledge of the clinical characteristics and management guidelines of bacterascites are limited. Recently, Oey et al reported that 123 patients with bacterascites from single centre were comparable to SBP patients with respect to prognosis …”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the study by Oey et al shows that bacterascites is a special form of ascites infection with a high mortality . Our goal should be to reduce this high mortality.…”
mentioning
confidence: 87%
“…Secondly, prognosis of patients with bacterascites was very poor in the study of Oey et al One‐month and one‐year mortality were 36% and 66%, respectively. These mortality rates were comparable to SBP patients from the same centre (34% and 77% respectively).…”
mentioning
confidence: 97%
See 1 more Smart Citation